Evaluation of the Effect of Topical Artemisia dracunculus Administration on Serum Levels of Selected Interleukins and Spleen Index in Imiquimod-Induced Psoriasis in Male Mice Compared to Clobetasol Propionate (Dermovate (R)) Ointment - M. Mohammed, Thamer; H. Mutlag, Shihab; A.Shihab, Bahaa (Iraqi Journal of Pharmaceutical Sciences, 2020)
Psoriasis is a long-lasting autoimmune disease that is characterized by swollen skin patches. Normally, these skin patches are dark, swollen, itchy and scaly. The single application of the innate TLR7/8 ligand Imiquimod (IMQ) in mice easily induces a dermatitis that closely resembles human psoriasis, critically dependent on the axis of IL-23/IL-17. Artemisia dracunculus prepared as an ointment and has been used topically to mice before imiquimod application. The results of the current study showed that A. dracunculus ointment can significantly reduce psoriasis area and severity index in (A. dracunculus ointment + imiquimod group as compared with both control group and (vehicle ointment + imiquimod) group.